2005
DOI: 10.1128/aem.71.9.5484-5493.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Dual-Species Bacterial Aggregates on Leaf Surfaces

Abstract: The spatial organization of cells within bacterial aggregates on leaf surfaces was determined for pair-wise mixtures of three different bacterial species commonly found on leaves, Pseudomonas syringae, Pantoea agglomerans, and Pseudomonas fluorescens. Cells were coinoculated onto bean plants and allowed to grow under moist conditions, and the resulting aggregates were examined in situ by epifluorescence microscopy. Each bacterial strain could be localized because it expressed either the green or the cyan fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 31 publications
2
71
1
Order By: Relevance
“…This results in spatially segregated microcolonies of competing strains with limited interactions and leads to coexistence of strains. Our observations of competitive interactions on the surface of U. australis are supported by recent reports on spatial segregation of epiphytic bacteria on leaf surfaces (40,43). The observations differ from the results of flow cell experiments in which P. tunicata was able to dominate and eventually remove certain competing strains (48).…”
contrasting
confidence: 54%
“…This results in spatially segregated microcolonies of competing strains with limited interactions and leads to coexistence of strains. Our observations of competitive interactions on the surface of U. australis are supported by recent reports on spatial segregation of epiphytic bacteria on leaf surfaces (40,43). The observations differ from the results of flow cell experiments in which P. tunicata was able to dominate and eventually remove certain competing strains (48).…”
contrasting
confidence: 54%
“…As expected, the treatment with phosphate-buffered saline did not present bacterial colonization (Figures 1 E and F). Monier & Lindow (2005a, 2005b report the importance of the aggregate formation for the protection of epiphytic population against desiccation, UV radiation, high temperatures and environmental fluctuations, besides the higher efficiency in nutrient acquisition and migration to regions of the phylloplane more favorable for survival. This work demonstrated that bacterial cells of P. macerans and B. pumilus form large aggregates on the tomato phylloplane.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they develop survival strategies in protected positions such as the trichomes base, inside substomatal chambers, hydathodes, and, especially, in between the depressions along the junctions of adjacent epithelial cells (Beattie & Lindow, 1999;Lindow & Brandl, 2003;Monier & Lindow, 2004, 2005a, 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality histopathology is time consuming and technically demanding, but it is highly rewarding to use superior modern instruments to observe specifically labeled cells, structures, or proteins in situ. This approach has been very productive in studies of animal pathogenesis but is underused by plant microbiologists (but see Newman et al, 2003;Meng et al, 2005;Monier and Lindow, 2005;Melotto et al, 2006;Nakaho and Allen, 2009). Microscopy studies often suggest hypothesisdriven experiments using defined mutants, and this combination can produce especially rapid advances, such as the fascinating discovery that X. fastidiosa uses twitching motility to move against the transpirational flow in xylem and colonize below an infection point (Meng et al, 2005).…”
Section: The Underexploited Power Of the Microscopementioning
confidence: 99%